Na tropach Wilkiego Collinsa = On the trail of Wilkie Collins - Berkan-Jabłońska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to Wilkie Collins as a precursor of the crime fiction genre. The works of thatVictorian writer are currently gaining popularity among the English researchers. In Poland, however,their reception has been very limited. It is a great pity since Collins's novels and short stories deserveattention as a number of artistic devices and ideas used by contemporary crime fiction can be foundin them; for instance, narrative polyphony, a specific design of the detective character, domesticateddread or social aspects of the investigation. The article goes over the chosen works of Collins withemphasis on their characteristics as crime fiction.
Keywords: Collins, William Wilkie (angielski powieściopisarz; 1824-1889); literatura angielska - tematyka; 19 w.